ОСОБЛИВОСТІ ПЕРЕХІДНИХ ПРОЦЕСІВ У КОЛАХ ДРУГОГО ПОРЯДКУ З НЕЛІНІЙНОЮ МОДЕЛЛЮ ІСКРОЕРОЗІЙНОГО НАВАНТАЖЕННЯ В УМОВАХ ПРИМУСОВОГО ОБМЕЖЕННЯ ЇХНЬОЇ ТРИВАЛОСТІ - Шидловська, Н.А.; Захарченко, С.M.; Черкаський, О.П. (Інститут електродинаміки НАН України, Київ, 2022)
In the Mathlab Simulink software environment a model of a second-order discharge-pulse system with a nonlinear description of the equivalent electrical resistance of a spark-erosion load was created. Under conditions of forced limitation of the duration of discharge pulses for a series of values of the inductance and capacitance of the discharge circuit, as well as the initial conditions in them, transients in the system are calculated. In groups of modes with fixed values of the initial voltage on the working capacitor and in groups of modes with fixed values of voltage amplitude of the free discharges on load, the dependences on duration of the discharge pulses of their energy, pulse power in the load, and the rate of its change are plotted and analyzed. It is shown that in both groups of modes for each set of parameter values of: the duration of the discharge pulses, the capacitance of the working capacitor and the initial voltage on it, there is a value of the inductance of the discharge circuit, which provides the highest values of the rate of change of the pulse power in the load. In the groups of modes with fixed values of the voltage amplitude of free discharges on the load, for the set of parameters described above, there are also values of the discharge circuit inductance that provide the highest values of energy and pulse power in the load. For three values of the inductance of the discharge circuit, the problems of increasing the above pulse parameters are graphically solved. References 27, figures 11.